Wage effect of over-education and mismatch in Malaysia: a random effect approach - Zainizam Zakariya (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper explores the ffict of education mismatch and earnings outcome in Malaysia by taking both over-education and mismatch byfield of study into account Based on 2007 Malaysia Productivity Investment Climate Survey (etcs), it is found that around 18%o and 28%, ofworkers employed in jobs for which they are over and under-educated, respectively. In terms of mismatch, about 52(% of workers are employed in jobs not corresponding to theirfield of study (1i% does not related and 35?(, no ipecificfield of study required). Close examination reveals that nearly twolhird of the overeducated are employed in jobs outside their ownfield of study. With respect to earnings outcomes, Random Effect (nz) models show that being overeducated and employed outside ownfield ofstudy resulted in earnings loss, betyveen 5 and 8o%for the former and 6 and l0%for the latter. Moreover, the wage penalty for being overeducated increases to roughly l40% to l7o% if working in jobs unrelated to theirfield of study. Greater earning loss may suggest that among the overeducated, they are heterogeneous of both schooling and workers. As such, the results imply that there are significant costs to selecting a major and then deciding to work in an occupation unrelated to the major since knowledge and skills acquired is not completely general and cannot simply be transferred to other occupations.